CCNA routing and switching portable command guide - Empson, Scott (Cisco Press, 2016)
Here are all the CCNA-level Routing and Switching commands you need in one condensed, portable resource. CCNA Routing and Switching Portable Command Guide is filled with valuable, easy-to-access information-and it's portable enough to use whether you're in the server room or the equipment closet. The guide summarizes all CCNA certification-level Cisco IOS Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Throughout, configuration examples give you a better understanding of how these commands are used in simple network designs. This book has been completely updated to cover all topics in the new ICND1 100-105, ICND2 200-105, and CCNA 200-125 exams. Use this quick reference resource to help you memorize commands and concepts as you work to pass the CCNA Routing and Switching certification exam. Coverage includes Network Fundamentals: Subnetting, VLSM, route summarization, cables/connections, CLI LAN Switching: Switch configuration, VLANs, VLAN trunking protocol, inter-VLAN communication, STP, EtherChannel Routing (IPv4/IPv6): Router configuration, static routing, RIPng, EIGRP/EIGRPv6, OSPFv2/OSPFv3 WAN: Point-to-point protocols, eBGP, GRE tunnels, QoS Infrastructure Services: DHCP, FHRP, HSRP, NAT Infrastructure Security: Switch port security, ACL traffic management, device hardening Infrastructure Management: Backup/restore, password recovery, CDP, LLDP, IOS tools, device monitoring, IOS licensing, troubleshooting Quick, offline access to all CCNA Routing and Switching commands for research and solutions --Logical how-to topic groupings for a one-stop resource --Great for review before CCNA Routing and Switching certification exams --Compact size makes it easy to carry with you wherever you go --"Create Your Own Journal" section with blank, lined pages enables you to personalize the book for your needs --"What Do You Want to Do?" chart inside the back cover helps you to quickly reference specific tasks This book is part of the Cisco Press Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco® certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press.
Includes index. - Online resource; title from title page (Safari, viewed June 2, 2016)
Keywords: Routing (Computer network management); Telecommunication -- Switching systems; Internetworking (Telecommunication); Routage (Gestion des réseaux d'ordinateurs); Télécommunications; Systèmes de commutation; Interconnexion de réseaux (Télécommunications); COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Telecommunication; Switching systems